If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 4 = 12a + 6 Reorder the terms: 4 + 2a = 12a + 6 Reorder the terms: 4 + 2a = 6 + 12a Solving 4 + 2a = 6 + 12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12a' to each side of the equation. 4 + 2a + -12a = 6 + 12a + -12a Combine like terms: 2a + -12a = -10a 4 + -10a = 6 + 12a + -12a Combine like terms: 12a + -12a = 0 4 + -10a = 6 + 0 4 + -10a = 6 Add '-4' to each side of the equation. 4 + -4 + -10a = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -10a = 6 + -4 -10a = 6 + -4 Combine like terms: 6 + -4 = 2 -10a = 2 Divide each side by '-10'. a = -0.2 Simplifying a = -0.2
| a*a(a-2b)+3b(a*a-4)= | | t+15=20 | | =-4x^3+18x | | 1/3n4 | | -2p+1=5 | | (5x+7)-(3x-1)=22 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i+2=0 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i=0 | | 2x^2+5x+3=15 | | 22x^2+5x+3=15 | | 0.5x+2.49=-.07x+6.69 | | 1=b-13 | | 3cos^2x=7sinx+5 | | X-52=100 | | 7x+9y=107 | | 2-3x=-2-2x | | 8-1/4z=1 | | 3,6*4/0,6*8 | | 6v=198 | | 4(x+5)-24=5x-13 | | 13+n=23 | | 25=a/b | | 15=2x+5x+3 | | (10w-9)(8w+7)= | | 2x^4-8x-3=0 | | 4y+5(5-y)-20+2y= | | A=3.1+-09b | | (2y+3)(7y+1)= | | lg(4x-2)=1 | | 10=v+1 | | X(x*x-1)=30 | | 14+x=8x |